In vitro Antibacterial and Antifungal Activities of Sorindeia madagascariensis and Albizia harveyi Stem Barks - Makoye, Paul Malaba; Mrutu, Sunday; Daniel, Innocent John; Mbunde, Mourice Nyangabo; Sempombe, Joseph; Mugoyela, Veronica (UI Scholars Hub, 2022)
The emerging multi-drug-resistant pathogens urge continuous searches for new antimicrobial agents. This study investigated the in vitro antibacterial and antifungal activities of the stem barks of two plants, Sorindeia madagascariensis and Albizia harveyi. Broth microdilution assay was used to determine the minimum inhibitory concentrations (MICs) of hydroethanolic extracts of the stem barks against selected bacteria and fungi. Both plant extracts exhibited activity against all tested microorganisms and their minimum inhibitory concentrations (MICs) against bacteria and fungi were from 1.67 to 5.00 mg/mL and from 1.67 to 10.00 mg/mL, respectively. This study reports the antibacterial and antifungal activities of the hydroethanolic extracts of the stem barks of both plants. Antifungal activity of A. harveyi is being reported for the first time. We therefore suggest further investigation of bioactive compounds from stem barks of A. harveyi and S. madagascariensis with antibacterial and antifungal activities.